The future of change: Roles, dynamics and functions for fishing communities in the management of Lake Victoria's fisheries - Geheb, Kim; Medard, M.; Kyangwa, M.; Lwenya, C. (2007)
This paper is based on five years of research around the shores of Lake Victoria carried out by the lake's Fisheries Research Institutes in collaboration with the Lake Victoria Fisheries Research Project. Based on this experience, the authors identify a series of difficulties, which impedes the effective management of the lake's fisheries. These relate to profound weaknesses in the current state-administered management of the lake along with difficulties transferring regulatory power to fishing communities, and problems establishing an adequate 'co-managerial' framework for the development and implementation of managerial action. The authors propose a management structure based on three levels of administration which have at their core 'beach committees,' and which serve as forums for negotiated managerial outcomes.